2014
DOI: 10.1002/bip.22498
|View full text |Cite
|
Sign up to set email alerts
|

Stability and degradation patterns of chemically modified analogs of apelin‐13 in plasma and cerebrospinal fluid

Abstract: Apelin is the endogenous ligand of APJ, which belongs to the superfamily of G protein-coupled receptors. In recent years, the apelin/APJ system has been detected in many tissues and emerges as a promising target for the treatment of various pathophysiological conditions. Pyr1-apelin-13 is the major isoform of apelin in human plasma; however its stability and proteolytic degradation pattern remain poorly understood. The aim of the present study was first to identify the cleavage sites of Pyr1-apelin-13 in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 35 publications
8
69
1
1
Order By: Relevance
“…In addition, Gerbier et al (33) showed that K17F and pE13F have a half-life in mouse plasma of 4.6 and 7.2 min, respectively, and Murza et al (42) showed that pE13F has a 14 min half-life in rat plasma. Regarding apelin-36, Japp et al (43) suggested from experiments conducted in healthy human subjects that the half-life of apelin 36 is lower than 5 min.…”
Section: Development Of Metabolically Stable Apelin Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Gerbier et al (33) showed that K17F and pE13F have a half-life in mouse plasma of 4.6 and 7.2 min, respectively, and Murza et al (42) showed that pE13F has a 14 min half-life in rat plasma. Regarding apelin-36, Japp et al (43) suggested from experiments conducted in healthy human subjects that the half-life of apelin 36 is lower than 5 min.…”
Section: Development Of Metabolically Stable Apelin Analogsmentioning
confidence: 99%
“…Numerous technologies, such as PEGylation (44, 45), palmytoylation (46) conjugation to albumin, N-terminal acetylation (33), C-terminal amidation (47), use of unnatural amino acids (15, 33, 42, 48), or main chain modifications (cyclization) (4951) have now been set up to increase the in vivo plasma half-life of peptides (52). Table 1 summarizes the pharmacological characteristics of the main metabolically stable apelin analogs described in this section.…”
Section: Development Of Metabolically Stable Apelin Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 cleavage occurred only in vivo. 59 Reproduced with permission from Biopolymers (Murza, A.; Belleville, K.; Longpre, J. M.; Sarret, P.; Marsault, E. Stability and degradation patterns of chemically modified analogs of apelin-13 in plasma and cerebrospinal fluid. 2014 , 102 , 297–303).…”
Section: Figurementioning
confidence: 99%
“…The plasma instability of apelin is due to the rapid degradation of the peptide [22,25,26,45] which results in significantly short plasma half-life (<8 min) [46]. Nanocarrier drug formulations have been found beneficial for the sustained delivery of therapeutic compounds in various cardiac disease [27–29].…”
Section: Introductionmentioning
confidence: 99%